Do Tertiary Dropout Students Really Not Succeed in European Labour Markets? - Sylke V. Schnepf (Institute for the Study of Labor (IZA), 2014)
Tertiary education has been expanding hugely over the last decades, so that tertiary dropout students will constitute a growing distinctive group in future labour markets. University dropout is regularly discussed as a 'negative' indicator in terms of reinforcing socio-economic inequalities and being a sign of university inefficiency. However, research on actual career trajectory of dropout students is virtually non-existent. Using data from the 2011 Programme for the International Assessment of Adult Competencies (PIAAC) this study first validates the uncommon self-reported measure of dropout used and compares the percentage of adults with tertiary dropout experience between OECD countries. Second, we examine whether tertiary dropout is a permanent decision as a considerable part of literature assumes. In a third step, we investigate characteristics of adults with dropout experience. Finally, we estimate the effect of dropout in terms of their employment status and success of entering managerial professions comparing results of logistic regressions and propensity score matching taking individuals' socio-economic and demographic background, work experience and cognitive skills into account. Results indicate that consistently across countries dropout is repeatedly a 'positive' indicator in the labour market. This is first due to the fact that the dropout decision is often not a permanent one as well as that for those adults who do not re-enrol into tertiary education labour market chances are better than for equally educated adults in about half of the countries examined.
Keywords: I21; 330; European countries; labour market chances; tertiary dropout; propensity score matching